MEDICAL ETHICS EDUCATION IN TURKEY; STATE OF PLAY and CHALLENGES - Perihan Elif Ekmekçi (Informascope, 2016)
ABSTRACT Medical ethics can be traced back to Hippocratic oat in antiquity. Last decade witnessed improvements in science and technology which attracted attention to the ethical impacts of the innovations in medicine. The need to combine medical innovations with a preservation of human values and to cultivate ethical competencies required by professionalism conceived medical ethics education in various levels in medical schools. Despite the diversities regarding teaching hours, methodology and content of the courses, medical ethics became a fundamental part of medical education around the world. In Turkey medical ethics education is given both in undergraduate and postgraduate levels. The high increase in the number of medical schools and shortfall of instructors who have medical ethics as their primary academic focus creates a big challenge in medical ethics education in both levels. Currently there are 89 medical schools in Turkey and only six medical schools are giving postgraduate medical ethics education. In 2010 only 33 of all medical schools could establish a separate department dedicated to medical ethics. There are no medical ethics courses embedded in residency programs. The quality and standardization of undergraduate medical ethics education has started but there are no initiatives to do so in postgraduate level.